Immobilization of trypsin on spent grains for whey protein hydrolysis - Rocha, Cristina M. R. (2011)
The aims of this work were to establish an efficient protocol for trypsin immobilization on spent grains and to assess the influence of the chosen protocol on whey protein hydrolysis. Trypsin was immobilized onto spent grain or modified spent grain, through adsorption and covalent attachment. The efficiency of immobilization and operation and storage stabilities of free and immobilized enzyme on the supports were studied. The enzyme activity, kinetic parameters and the peptide profile of the protein hydrolysates from free and immobilized enzyme were also analysed. The best activity retention was achieved with the immobilization on spent grains through multipoint covalent attachment using glycidol. This carrier showed also very good storage and operational stability (above 90%). Trypsin immobilized on spent grains showed significant activity towards whey proteins. The immobilized enzyme was slightly more stable than the free enzyme at temperatures between 50 °C and 60 °C allowing its use at a broader range of temperatures. The peptides formed with free enzyme and enzyme immobilized on spent grains were generally similar. However, significant differences existed in the amount of native proteins in the hydrolysates and in the relative amount of smaller peptides.